Lab coat 1 - Mohd Ghazali, Asmal Hamidah; Maliki, Nur Intan Idayu; Othman, Siti Amira (Penerbit UTHM, 2020)
The lab coats is an inevitable in making sure a safe and healthy workplace are attained. It is a responsible for everyone working in environment that incorporate hazardous chemical, radioactive materials and biological agents or greater to take a significant action in making sure lab coats as one of the vital component while working. Furthermore the Occupational Safety and Health Act 1994 require authority of a workplace to take action upon reasonable situation ones in. Thus lab coats acts as a medium of protection to the one involved.